2015 Seventh International Workshop on Quality of Multimedia Experience (QoMEX) 2015
DOI: 10.1109/qomex.2015.7148088
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of HEVC and VP9 video compression in real-time applications

Abstract: Abstract-Video consumption over Internet has increased significantly over the recent years and occupies the majority of the overall data traffic. To decrease the load on the Internet infrastructure and reduce bandwidth taken by video, higher efficiency video codecs, such as H.265/HEVC and VP9, have been developed. The availability of these two new competing video coding formats raises the question of which is more efficient in terms of rate-distortion and by how much they outperform the current state-of-the-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…Video coding affects the quality perception of video streaming as stated in literature [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. A variety of video coding standards have been analysed in this context, such as H.264/ advanced video coding (AVC) or H.265/HEVC.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Video coding affects the quality perception of video streaming as stated in literature [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. A variety of video coding standards have been analysed in this context, such as H.264/ advanced video coding (AVC) or H.265/HEVC.…”
Section: Related Workmentioning
confidence: 99%
“…It has been shown that H.265/HEVC allows 50% higher compression than its predecessor H.264/AVC without changes in subjective quality perception [23,24,32,33]. In addition, it has been realized that H.265/HEVC has 6dB higher peak signal to noise ratio (PSNR) than H.264/AVC due to variable length of code blocks [24,25]. Furthermore, H.265/HEVC enables a higher degree of variation of codec parameters, such as coding block size, motion vector size, etc.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [2] VP9 was claimed to be inferior to HEVC/H.265 by different statistics, whereas [3] revealed a similar performance between the two. To benchmark the performance of HEVC/H.265 and VP9, both objective and subjective assessments have been carried out in [4] and [5], with bitrates ranging from low to high corresponding to very low up to transparent video quality. In [4] a clear advantage of HEVC/H.265 over VP9 with almost twice as much bitrate savings was reported when using the low delay configuration on high definition (HD) and ultra high definition (UHD) video content.…”
Section: Introductionmentioning
confidence: 99%
“…To benchmark the performance of HEVC/H.265 and VP9, both objective and subjective assessments have been carried out in [4] and [5], with bitrates ranging from low to high corresponding to very low up to transparent video quality. In [4] a clear advantage of HEVC/H.265 over VP9 with almost twice as much bitrate savings was reported when using the low delay configuration on high definition (HD) and ultra high definition (UHD) video content. Similar results were obtained in [5] using UHD video content assuming a broadcasting configuration, noting a competitive performance of VP9 for some synthetic video.…”
Section: Introductionmentioning
confidence: 99%